Verlen in the Interlinear Translation and in Translation: Creative Laboratory of Fyodor Sologub - Vsevolod E. Bagno; Tatyana V. Misnikevich (Studia Litterarum)
This article examines the development of the translation manner of Fyodor Sologub. The study of the poet’s archive makes it possible to highlight a number of preparatory materials for Sologub’s translations from Paul Verlaine, in particular, interlinear translations. Sologub’s experiments with interlinear translations, which in his case represent a hybrid genre (interlinear translations that include a large number of different dictionary variants of words) are of great importance for the theory, history, and practice of literary translation. Using specific examples, the essay demonstrates that Sologub worked not just with the original text, traditional interlinear translation, and written out words. He employed his “expanded” interlinear translation where he could freely navigate, choose and rearrange words, try their “sound” while seeking to keep their meaning. The authors argue that Sologub’s translating method consisted in selecting Russian words on the basis of the interlinear translation that not only conveyed the original but also made it possible to create a new lexical, grammatical, metric, phonetic, and emotional unity close to the translator’s worldview mindset and aesthetic views.